Midwives’ views regarding educational needs in perimenopausal health and care - Tork- zahrani, S; Lotfipur- Rafsanjani, M; Ahmadi, M; Alavi- Majd, H (Advances in Nursing & Midwifery, 2007)
Abstract Background: Today, due to medical improvements, 95% of women reach menopausal age. As a result, health providers should properly educate these women regarding physical and psychological changes of this period. Continuing education of midwives as health care providers is a necessity in this respect. Hence, assessing educational needs of them becomes a determinant factor in guaranteeing efficient educational program. Accordingly, assessing these needs is likely to support national health and wellbeing. Purpose: This descriptive study was conducted to determine the views of midwives regarding health education and care during perimenopausal period in Rafsanjan in 2006. Methods: All 97 midwives working in private and governmental sectors in Rafsanjan were chosen. Data were collected using a questionnaire consisted of two parts: demographic characteristics and items related to midwives’ views regarding educational needs. The validity of the questionnaire was determined by content validity and its reliability by test-retest. Results: Findings indicated that the most urgent need was nonmedical treatments in menopause (80%). The next priority of midwives was sexual problems (76.25%), medical and hormonal treatments (75.75%), counseling during menopausal period (75.75%), exercise during menopausal period (72%), recognition of signs and symptoms of menopause (58%) and nutrition in menopause (53.5%). Conclusion: Recently, special attention has been given to menopause. Our findings showed that nonmedical treatments in menopause are the first priority of midwives regarding educational needs. This verifies nonmedical approaches in treatment during past decades. It is expected to use these approaches in educational planning of midwives. To make continuing education programs for midwives efficient, studies on assessing educational needs in other aspects of midwifery are warranted. Key words: Educational needs assesment, Menopause, Midwives, Complementary therapies, Health education.